Question #74225

2 Answers

It is proved below;

Explanation:

L.H.S=sinA+tanA

=tanA(sinA/(tanA)+1)
=tanA(sinA/(sinA/cosA)+1)
=tanA((color(green)cancelsinAxxcosA)/color(green)cancelsinA+1)

=tanA(cosA+1)=tanA(1+cosA)=R.H.Scolor(blue)[[Proved.]

Dec 18, 2017

"see explanation"

Explanation:

"using the "color(blue)"trigonometric identity"

•color(white)(x)tanA=sinA/cosA

"consider the right hand side"

tanA(1+cosA)

=tanA+sinA/cancel(cosA)xxcancel(cosA)

=sinA+tanA

="left hand side "rArr"verified"